Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Minat Kunjungan Ulang Pasien Rawat Jalan Rumah Sakit TK III dr. Bratanata Jambi - Amrina, Dwi; Listautin, Listautin; Afriany N, Renny (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2026)
The quality of health services plays an important role in the reputation of health service institutions in the community. Good quality of service and facilities can increase patient satisfaction and encourage patients to make repeat visits. This study aims to analyze the influence of service and facility quality on the interest of outpatient revisits in hospitals TK III dr. Bratanata Jambi. The research approach uses a quantitative method with an associative study design.. The research sample amounted to 100 new outpatient respondents who were selected using purposive sampling techniques. Data were collected through questionnaires and observations, analysis using Chi-Square test, Partial T test and F test with the help of SPSS version 25. The results of the analysis showed that the quality of service had a significant effect on the interest of patient revisits with a value of p = 0.001 (<0.05), and facilities showed a significant influence with a value of p = 0.000 (<0.05). A simultaneous test (F test) confirmed that the quality of service and facilities together had an effect on the interest of repeat visits (F value = 6.755, p < 0.05). The quality of services and facilities has a significant effect on the interest of outpatient revisits at the hospital TK III dr. Bratanata Jambi.